Biophysical aspects of handcycling performance in rehabilitation, daily life and recreational sports; a narrative review. Issue 24 (20th November 2021) - Kraaijenbrink, Cassandra; Vegter, Riemer; de Groot, Sonja; Arnet, Ursina; Valent, Linda; Verellen, Joeri; van Breukelen, Kees; Hettinga, Florentina; Perret, Claudio; Abel, Thomas; Goosey-Tolfrey, Victoria; van der Woude, Lucas
Abstract: Aim: In this narrative review the potential and importance of handcycling are evaluated. Four conceptual models form the framework for this review; (1) the International Classification of Functioning, Disability and Health; (2) the Stress-Strain-Capacity model; (3) the Human-Activity-Assistive Technology model; and (4) the power balance model for cyclic exercise. Methods: Based on international handcycle experience in (scientific) research and practice, evidence-based benefits of handcycling and optimization of handcycle settings are presented and discussed for rehabilitation, daily life and recreational sports. Results: As the load can be distributed over the full 360 ° cycle in handcycling, peak stresses in the shoulder joint and upper body muscles reduce. Moreover, by handcycling regularly, the physical capacity can be improved. The potential of handcycling as an exercise mode for a healthy lifestyle should be recognized and advocated much more widely in rehabilitation and adapted sports practice. The interface between handcycle and its user should be optimized by choosing a suitable person-specific handcycle, but mainly by optimizing the handcycle dimensions to one's needs and desires. These dimensions can influence efficient handcycle use and potentially improve both endurance and speed of handcycling. Conclusion: To optimize performance in rehabilitation, daily life and recreational sports, continued and more systematic research is required. Implications for rehabilitation: Handcycling allows users to travel farther distances at higher speeds and to train outdoors. It should be recognized as an alternative exercise modality for daily outdoor use, also already in early rehabilitation, while it contributes to a healthy lifestyle. To individualize handcycle performance, the user-handcycle (assistive device) interface as well as the vehicle mechanics should be optimized to minimize external power and reduce friction, so that the upper body capacity can be efficiently used. To optimize handcycling individual performance, both the physiological and biomechanical aspects of handcycling should be considered when monitoring or testing handcycle exercise.